“AN INCREASING DISQUIET DUE TO THE EFFECT OF THE PANDEMIC ON PHYSICAL AND MENTAL HEALTH OF MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY” - Begum, Jarina; Shaik, Firoj Unnisa; Bose, Saptarishi; Ali, Syed Irfan (Student's Journal of Health Research Africa, 2025)
Background The COVID-19 outbreak created havoc, resulting in significant morbidity and mortality. Due to the shift of lectures and virtual consultations online, the education and healthcare industries were vastly affected. The present study was planned among medical students to identify the impact of a pandemic on their physical and mental health. Methodology A prospective cross-sectional study was conducted among 115 MBBS undergraduate students. The data was collected through an online questionnaire Data thus collected was analyzed using descriptive and thematic analysis. Results Amongst all, 66.1% were females, although 67% had normal BMI, and 24.3% were overweight. 44.34% were active online for more than 10 hours, however, only 49.56% preferred to spend it on academics. 83.5% of students faced difficulties in their studies. 69.6% of students perceived their eating habits to change during the pandemic & 81.7% of students reported changes in their sleeping habits. Most students (67%) noticed weight gain during the lockdown. There are various physical symptoms developed during the lockdown. 63.5% of students agreed that the shift to online classes was the reason for their stress. 52.2% were affected by COVID-19, and 87.8% perceived that going to crowded places was stressful. Conclusion The study concluded that overall, students had a mixed perception of the changed lifestyle due to the pandemic. However, it had few positive (availability of time, family bonding, scope for creativity) and more negative (stress and anxiety, likewise, weakness, eye strain, headache, and weight gain) effects on their physical and mental health. Recommendations The current study recommends regular evaluation of the medical student’s mental and physical health.